Rethinking side effects of accountability in education: Insights from a multiple methods study in four German school systems - Thiel, Corrie; Schweizer, Sebastian; Bellmann, Johannes (Education Policy Analysis Archives, 2017)
Based on a research project comprising data from an interview study and a survey with teachers and school principals in four German federal states (Bundesländer), this paper questions the claim that the side effects of accountability in education are bound to high-stakes contexts, and also provides evidence of side effects occurring in no- and low-stakes contexts. The findings suggest that side effects cannot be fully explained by certain implementation features of accountability regimes (e.g. high stakes), but should rather be understood as a result of implementation features as well as systematic effects of accountability in education.